Multi-item EOQ model for fresh fruits with preservation technology investment, time-varying holding cost, variable deterioration and shortages. Issue 2 (3rd April 2017) - Dhandapani, J.; Uthayakumar, R.
Abstract: In a fruit wholesale shop, a fruiterer needs to maintain huge inventory of different ranges of fruit items for customers because of uncertainty in consumer preferences and behaviour. But demand of them may differ and different EOQ models for each item are required for optimal level of EOQ. This paper presents a single inventory model to assimilate these varieties. It is assumed that many fruit items bear constant rate of deterioration, some are with time proportional deterioration and some do not deteriorate. To control deterioration of the units in inventory, the advanced preservation technology is considered. The proposed single inventory model of this paper incorporates composite and heterogeneous features of multiple items and presents analysis for obtaining optimal level for output model parameters.